Determinants of life satisfaction among Japanese agricultural workers - Wei, Chang-Nian (Springer-Verlag, 2000)
The purpose of this study was to investigate the factorial structure of life satisfaction in agricultural workers. One hundred and sixty-five (87 males and 78 females) agricultural workers mainly engaged in plastic greenhouse cultivation in southern Japan, ranging in age from 19 to 72 years (mean = 44.3 years), completed a questionnaire. Scores of life satisfaction showed a higher tendency in males than in females, and those in elders were higher than in younger people. Conversely, females showed higher stress scores than males, and younger people’s score were higher than the elders. Multiple regression analysis was performed to analyze the factorial structure of satisfaction. It is suggested that the level of life satisfaction is positively related to social support, and is negatively related to the impact of stressful life events, globally perceived stress and subjective symptoms of ill health. Stress levels depended on factors concerning the psychological demands of work, work posture, work hours and work environment. Different factorial structures were observed between female and male workers. Findings from this study suggest that a strong social support network may assist in enhancing life satisfaction. Furthermore, the ill health and stress experienced in agricultural work were associated with a reduced life satisfaction.